Determinants of successful ski-jumping performance - Komi, P. V.; Virmavirta, M. (Biomechanics in Sport: Performance Enhancement and Injury Prevention: Volume IX of the encyclopaedia of sports medicinean IOC Medical Commission publicationin collaboration with the International Federation of sports medicine, 2000)
Ski-jumping is an exciting sport requiring complexskills and involving several phases-inrun, takeoff, flight and preparation for landing-each of whichhas importance to the length of the jump. In general the performance includes both ballistic and aerodynamic factors. The ballistic factors include release velocity and release position from the take-off table, whereas aerodynamic factors during take-off and flight influence the gliding properties of the jumper/ski system (velocity, suit design, surfacearea, posture of the jumper/ski system, turbulence, and resisting and lifting forces). It is important to realize that both ballistic and aerodynamic factors place special demands on the jumper so that he canoptimally maximize the vertical lift and minimizethe drag forces.Takeoff is probably the most crucial phase for the entire ski-jumping performance. The purpose of the takeoff is to increase the vertical lift and simultaneously maintain or even increase the horizontal release velocity. It is therefore important to emphasize that it is the jumper and his or her ability to perform a skilful takeoff and the subsequent flightphase, which finally determines the length of thejump. For this reason great demand is placed on the jumper`s neuromuscular system, especially becauseof the unusually short time available for execution of the takeoff. This chapter makes an attempt to review factors that are involved in ski-jumping performance. Special effort will be made to characterize the takeoff action and link this to the relevant neuro-muscular functions of the jumper. Techniques of measurement of the actual takeoff forces have improved considerably during the last two decades. These aspects are also described, both methodologically and also with respect to the neuromuscular requirements and especially how they are related to the length of the jump. Integration of muscle activation patterns with the takeoff technique is also relevant for an understanding of ski-jumping performance. The present review is a follow-up of a previous article on the same topic.